1992
DOI: 10.1111/j.1365-2249.1992.tb06484.x
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1 anti-trypsin and CD30 expression occur in parallel in activated T cells

Abstract: SUMMARYWe have performed an immunotiistochemical study of immunobtastic T celt lymphoma and enteropathy-associated T cell lymphoma for alpha-1 anti-trypsin and CD30. Cytoplasmic staining for al anti-trypsin is present in the malignant cells in both types of T cell neoplasm which also express CD30, a marker of lymphoid activation. Peripheral blood T lymphocytes on stimulation with mitogen also show granular cytoplasmic expression of al anti-trypsin. Time course studies show that this parallels the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…[18][19][20][21] Although α1-AT in the blood is mainly produced by the liver, a large number of studies have found that many extrahepatic tissues, including intestinal epithelial cells, alveolar epithelial cells, pancreatic microvascular endothelial cells, monocytes, T lymphocytes, and articular cartilage, can also secrete α1-AT. [22][23][24][25][26] In addition, it has been demonstrated that renal tubular epithelial cells can express α1-AT at both the protein and mRNA levels, and the expression can be upregulated by LPS. 27 Therefore, we hypothesized that α1-AT might also be involved in the inflammatory processes involved in the progression of DKD.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Although α1-AT in the blood is mainly produced by the liver, a large number of studies have found that many extrahepatic tissues, including intestinal epithelial cells, alveolar epithelial cells, pancreatic microvascular endothelial cells, monocytes, T lymphocytes, and articular cartilage, can also secrete α1-AT. [22][23][24][25][26] In addition, it has been demonstrated that renal tubular epithelial cells can express α1-AT at both the protein and mRNA levels, and the expression can be upregulated by LPS. 27 Therefore, we hypothesized that α1-AT might also be involved in the inflammatory processes involved in the progression of DKD.…”
Section: Introductionmentioning
confidence: 99%
“…It may also exert an effect on autophagy, thereby affecting endoplasmic reticulum function 30. At the cellular level, peripheral blood T lymphocytes stimulated with a mitogen display granular cytoplasmic expression of AAT 31. AAT reduces a detrimental tumor necrosis factor alpha-dependent effect on lymph nodes in adipose and pancreatic tissues 32.…”
Section: Discussionmentioning
confidence: 99%